Effect of Barrier Film Type and Iron-based Oxygen Scavenger on Physico-Chemical, Microbiological and Sensory Quality of Refrigerated Fresh Pork Chunks Tray-Packaged in Food Grade Polypropylene Trays - Dhineshkumar, V.; Devadason, I. Prince; Mendiratta, S. K.; Kumar, R. R.; Agarwal, R. K. (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Retail packaging of fresh red meat in India is largely confined to low-barrier LDPE pouches that offer poor protection against oxidative and microbial deterioration during chilled display. The objective of the present investigation was to evaluate the effect of four food-grade wrap films of differing oxygen and water-vapour transmission rates (LDPE, LLDPE, HDPE and PVC) with and without an iron-based oxygen scavenger sachet (O-SORB U100, 2.5 g) on the storage stability of deboned fresh pork chunks tray-packaged in food-grade polypropylene trays at 4±1 °C. Eight treatments were evaluated and physico-chemical, microbiological and sensory parameters were monitored on day 0, 5 and 8 of storage. By day 8, control LDPE-packaged chunks were unacceptable, with pH 6.99 ± 0.02, TBARS 1.39 ± 0.04 mg MDA/kg, extract release volume of only 14.88 ± 0.27 mL and total plate count of 5.88 ± 0.09 log CFU/g. In contrast, the THDPE treatment (HDPE wrap film plus oxygen scavenger) retained acceptable quality (pH 6.16 ± 0.01, TBARS 0.64 ± 0.01 mg MDA/kg, ERV 28.25 ± 0.11 mL, total plate count 4.67 ± 0.05 log CFU/g) and the highest sensory acceptance among all eight treatments. The HDPE wrap film combined with an in-pack oxygen scavenger extended the refrigerated shelf life of fresh pork chunks from 5 days to 8 days, suggesting a feasible upgrade pathway for chilled pork retailing in tropical markets.